Analisis Hukum dan Syariah dalam Budaya Digital: Tantangan dan Peluang di Era Teknologi - Rahmawati, Fina (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2023)
This research aims to examine the legal and Sharia challenges in the context of digital culture. The research method used is literature analysis and literature review. In this study, it was found that the development of digital technology has significant implications for the fields of law and Sharia, especially in the context of digital culture. Some of the challenges faced include issues of privacy, data security, validity of online transactions, as well as ethical and moral issues in the use of digital technology. The research results show that law and Sharia must continue to evolve to cope with the rapid changes in digital culture. This involves a deep understanding of the principles of law and Sharia and their application in the digital context. Furthermore, it is important for legal and Sharia practitioners to address emerging challenges in the digital culture, including engaging in collaborations among legal, Sharia, and technology experts to tackle complex issues. This research contributes to the understanding of legal and Sharia challenges in the digital culture and provides a basis for policy-making and relevant regulatory development to address the rapidly changing digital culture. This research is expected to provide guidance and direction for legal, Sharia, and technology practitioners in navigating the evolving digital culture